O-252 Next generation sequencing analysis of the seminal microbiome in male partners of women with idiopathic recurrent pregnancy loss: results of a prospective cohort study. (30th June 2022) - Farahani, L; Mowla, S; Tharakan, T; Lee, Y; Kundu, S; Khanjani, S; Sindi, E; Rai, R; Regan, L; Ramsay, J; Bennett, P; Dhillo, W; et al.
Abstract: Study question: Is there an association between the semen microbiome, seminal reactive oxygen species (ROS) and DNA fragmentation in men with recurrent pregnancy loss (RPL)? Summary answer: This pilot study outlines the subtle role that microbiota play in influencing ROS and sperm DNA damage for male partners of women with RPL What is known already: RPL is defined as the loss of two or more consecutive pregnancies. This devastating condition impacts approximately 1% of couples. Paternal causes are not routinely screened for and an underlying cause is not found in up to 50% of cases. Recent studies have reported an association between elevated seminal ROS and sperm DNA fragmentation in the male partner, and RPL. We hypothesised that seminal microbiota contribute to increased ROS and sperm DNA damage. To test this, we investigated the relationship between seminal bacterial composition and ROS levels in men with proven fertility versus men with a history of RPL. Study design, size, duration: We conducted a prospective, case-control study and recruited participants between November 2018 and March 2020 at Imperial College Healthcare NHS Trust. A total of 109 men participated in the study; 46 men with RPL and 63 men with proven fertility and no history of RPL. Each participant attended for a single study visit which consisted of a full medical history, assessment of testicular volume, height, weight, blood samples and production of a semen sample. Participants/materials, setting, methods: Routine semen analysis (WHO) and endocrine and lipid profiles were performed for all patients. Semen ROS and DNA fragmentation were performed (luminol and TUNEL methodologies, respectively). ROS were classified as high (>3.77 RLU/s) or low (<3.77 RLU/s). Metataxonomic profiling of samples was performed using Illumina Miseq-based sequencing of the V1-V2 hypervariable regions of bacterial 16S rRNA gene amplicons. Multivariate and univariate modelling was performed to explore associations between metataxonomic profiles, ROS levels and clinical metadata. Main results and the role of chance: Men with RPL had higher mean semen volume (p = 0.02) and increased prevalence of high ROS (p = 0.02, Fisher's exact) compared with controls; but other clinical characteristics were similar between groups. A total of 3, 700, 136 high quality sequence reads were generated for the dataset with an average of 33, 946 reads/sample. Hierarchical clustering of bacterial genera relative abundances identified 4 distinct microbial signatures characterised by high relative abundance of 1. Streptococcus, 2. Lactobacillus and Gardnerella, 3. polymicrobial (including Prevotella), and 4. Corynebacterium and Finegoldia. Prevalences of these groups were similar in control and RPL groups (p = 0.11). Additionally, no association between the bacterial genera groups and elevated ROS, DNA fragmentation, or clinical factors such as age, ethnicity, or semen volume were observed (chi-square tests). At species taxonomy level relative abundance of L. crispatus was higher in controls compared to RPL, but did not withstand false discovery rate correction for multiple testing (p = 0.006, q = 0.67). Higher relative abundance of Microbacterium was detected in semen samples with high DNA fragmentation (p = 8.7E-4, q = 0.08). This relationship was even stronger within the RPL cohort (p = 2.8E-5, q = 0.002). No significant enrichment of specific taxa was observed between high or low ROS samples however, low ROS was associated with Corynebacterium relative abundance >20%. Limitations, reasons for caution: More patients are required to enhance statistical power. Duplicate sample collection may establish the robustness of seminal compositions observed. Time since last sexual intercourse samples may affect the analysis. Concomitant analysis of the vaginal microbiome of female partners may improve our understanding of how partners may affect each other's fertility. Wider implications of the findings: Our data suggests interactions between microbiota composition, ROS and sperm DNA damage which may be implicated in the pathogenesis of recurrent miscarriage. Further studies are needed to determine if seminal microbiota play causal roles in RPL, and whether interventions modifying the seminal microbiome may modify pregnancy outcomes in affected couples Trial registration number: not applicable